Dosage compensation and meiotic sex chromosome inactivation are maintained under relaxed selection - Darren J. Parker; Zoé Dumas; Rocío Gómez; Jean-Marc Aury; Marjorie Labedan; Patrick Tran Van; Benjamin Istace; Corinne Cruaud; Karine Labadie; Benjamin Noel; Susana Freitas; Jelisaveta Djordjevic; et al. (Proceedings of the National Academy of Sciences, 2026)
Dosage compensation and meiotic sex chromosome inactivation (MSCI) are key mechanisms regulating gene expression from the X chromosome in male-heterogametic species. While the convergent evolution of these mechanisms is well documented, their evolutionary fate under relaxed selection remains poorly understood. Here, we test whether dosage compensation and MSCI persist following three independent transitions to parthenogenesis in stick insects, where selection on male phenotypes is relaxed. Using rare males occasionally produced by parthenogenetic females, chromosome-level genome assemblies, RNA-seq from multiple tissues, and immunocytochemistry, we find that dosage compensation is fully conserved across all seven studied somatic tissues. This is even the case in the oldest, approximately 1.5 My old all-female lineage and for tissue-specific genes for which dosage variation is not expected to be very deleterious. Meiotic X inactivation in the germline is also conserved. Surprisingly, however, expression data and cytological markers indicate that MSCI signatures are even stronger in parthenogenetic males, a pattern likely driven by prolonged autosomal transcription during meiosis. These results indicate that X-targeting dosage compensation and MSCI are highly stable over evolutionary time and may be maintained in all-female lineages by a combination of evolutionary constraint, pleiotropy, or very weak selection, whereas autosomal expression during meiosis shifts rapidly under relaxed selection.